Resolution of expert council «Prospects of OM-85 application in the therapy of chronic rhinosinusitis» - V. M. Svistushkin; O. V. Karneeva; S. V. Ryazantsev; A. Yu. Ovchinnikov; H. T. Abdulkerimov; O. V. Kalyuzhin (Лечащий Врач)
The prospects of treating patients with chronic rhinosinusitis were discussed, as well as the possibilities of prevention and complex therapy of the exacerbations of this disease.